Extraction of an Infected Active Fixation Coronary Sinus Lead with the Aid of a Tissue Stabilizer - Stefania Blasi; Maurizio Levantino; Luca Paperini; Maria Grazia Bongiorni; Uberto Bortolotti (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
We present a 49-year-old man who required extraction of a cardiac resynchronization device due to lead infection. While 2 leads were successfully retrieved by a transvenous approach the third one with active fixation and entrapped into a coronary sinus side-branch, required surgical intervention. During the operation, performed on cardiopulmonary bypass on a beating heart, lead extraction was greatly facilitated by employment of a tissue stabilizer routinely used for off-pump coronary surgery.